The Impact of Pharmacist-Led Education on Patient Statisfaction in Pharmaceutical Service for Type 2 Diabetes Mellitus: A Cross Sectional Study in Two Hospital in Ambon City - Ipaenim, Nurjianti; Prima, Sylvia Rizky (Riviera Publishing, 2025)
Type 2 Diabetes Mellitus (T2DM) is a growing public health concern that requires effective management, including patient education. Although pharmacist-led education is recognized as important in diabetes care, evidence on its impact on patient satisfaction with pharmaceutical services in resource-limited areas like Maluku Province, Indonesia, is limited. This study evaluated the effect of pharmacist-led education on patient satisfaction among T2DM outpatients in Ambon City. Using a prospective cross-sectional design, 300 patients from RSU Al Fatah and Rumkit Tk II Prof. Dr. J.A. Latumeten hospitals participated. Data were collected over three months (November 2024 to January 2025) with the Patient Satisfaction with Pharmacy Services (PSPS) questionnaire. Participants were split into two groups: one received an e-booklet plus pharmacist education (n=150), while the other received the e-booklet only (n=150). Results showed a significant improvement in satisfaction scores for the education group, from a mean of 85.84 (pretest) to 215.16 (posttest), compared to a smaller increase in the non-education group, from 130.43 to 170.57. Statistical tests (Mann-Whitney U and Wilcoxon W) confirmed significant differences (p<0.001) pre- and post-intervention, with greater improvement seen in the education group. These findings suggest pharmacist-led education substantially enhances patient satisfaction in T2DM pharmaceutical services. Integrating such education into healthcare could improve treatment adherence and outcomes. Future studies should assess long-term health impacts and cost-effectiveness.